Overdose beliefs and management practices among ethnic Vietnamese heroin users in Sydney, Australia - Maher Lisa; Ho Hien T (BMC, 2009)
Abstract Background Ethnic Vietnamese injecting drug users (IDUs) in Australia draw on a range of beliefs and etiologic models, sometimes simultaneously, in order to make sense of health and illness. These include understandings of illness as the result of internal imbalances and Western concepts of disease causation including germ/pollution theory. Methods Observational fieldwork and in-depth interviews were conducted between 2001 and 2006 in neighbourhoods characterised by high proportions of Asian background IDUs and street-based drug markets. Eligibility criteria for the study were: 1) ethnic Vietnamese cultural background; 2) aged 16 years and over and; 3) injected drugs in the last 6 months. Results Participants commonly attempted to treat heroin overdose by withdrawing blood (rút máu) from the body. Central to this practice are cultural beliefs about the role and function of blood in the body and its relationship to illness and health. Participants' beliefs in blood were strongly influenced by understandings of blood expressed in traditional Chinese and Vietnamese medicine. Many participants perceived Western drugs, particularly heroin, as "hot" and "strong". In overdose situations, it was commonly believed that an excessive amount of drugs (particularly heroin) entered the bloodstream and traveled to the heart, making the heart work too hard. Withdrawing blood was understood to reduce the amount of drugs in the body which in turn reduced the effects of drugs on the blood and the heart. Conclusion The explanatory model of overdose employed by ethnic Vietnamese IDUs privileges traditional beliefs about the circulatory, rather than the respiratory, system. This paper explores participants' beliefs about blood, the effects of drugs on blood and the causes of heroin overdose in order to document the explanatory model of overdose used by ethnic Vietnamese IDUs. Implications for overdose prevention, treatment and management are identified and discussed.